Upaya Menerapkan 5M melalui Peran Anak Sejak Dini dalam Masa Pandemi Covid-19 - Qurratul A'yun; Kinanatul Qomariyah (Universitas Pahlawan Tuanku Tambusai, 2021)
Community Service revealed that Health Counseling for the Community and the application of 5M in daily life, instilling the value of caring for oneself and the surrounding environment and implementing clean and healthy living behavior from an early age, by always wearing masks outside the room, washing hands properly and It is true that maintaining a safe distance away from crowds and reducing mobility is important to the community, because this activity can raise public awareness in implementing clean and healthy living behaviors. This is one way to prevent and suppress the spread of the COVID-19 virus. This community service is in the form of health education for students of SDN 1 Jarin Pademawu Pamekasan. Community education involving 80 students was carried out with various lectures and discussions, as well as demonstrations on the 5M Health Protocol. The results obtained from community service are that this activity is expected to be implemented in an effort to improve healthy and clean lifestyle habits, so as to reduce the spread of the COVID-19 virus.